Regulatory Framework on IPR in Indonesia: Overview and Preliminary Assessment on the RCEP-IP Chapter - Karina, Eva Novi (Global and Policy Journal of International Relations, 2019)
In respect to the Regional Comprehensive Economic Partnership (RCEP) talks, Indonesia, the ASEAN coordinator for what will be the world's largest free trade pact, has acclaimed the substantial progress in negotiations, which has seen leaders agree to complete the deal this year. On the 33rd ASEAN Summit held in 2018, President Joko Widodo had stressed the importance of a mandate to agree on the RCEP. However, one question needs to bring to light is whether Indonesia's determination has been supported by adequate preparedness to comply with various binding provisions, especially the IPR regime designed to go beyond WTO TRIPs. In an effort to answer that question, this article will be focused on examining the IPR regulatory framework in Indonesia and to what extent it is compatible with the anticipated IPR provision based on the leaked draft of RCEP IP Chapter. Keywords: RCEP, TRIPs Plus, Intellectual Property Right, ASEAN, Indonesia DOI : https://doi.org/10.33005/jgp.v7i01.1816